Azhari, Ainul FILOSOFI PENDIDIKAN AGAMA ISLAM MENURUT AL-GHAZALI: : Integrasi Spiritualitas Dan Pengetahuan - Azhari, Ainul; Hotimah, Husnul (Universitas Islam Syekh-Yusuf, 2024)
The philosophy of Islamic religious education according to Al-Ghazali reflects a harmonious integration between spirituality and knowledge. Al-Ghazali, a famous medieval Islamic scholar, viewed education as a means to achieve the balanced goals of spirituality and knowledge. Al-Ghazali's thoughts became the basis for the development of a holistic Islamic education system. This research is qualitative research that is descriptive analytical in nature. Data collected through observation, interviews and documentation. The method applied in this research is a library search and the data analysis technique uses content analysis, because this research relies on text and aims to provide a description of the research results. The results of this research show that the integration of spirituality in Islamic religious education emphasizes the importance of developing students' character and morality. Al-Ghazali emphasized that education is not only about mastering knowledge, but also about self-transformation towards moral and spiritual perfection. Good Islamic religious education must be able to guide students to achieve spiritual awareness, adherence to religious values, and development of an Islamic personality. Apart from that, the integration of knowledge in Islamic religious education according to Al-Ghazali emphasizes the importance of aligning science with Islamic values. Education must help students understand the world holistically, including spiritual, moral and intellectual aspects. Al-Ghazali refers to the idea that science without spirituality can lead to moral paralysis and loss of the true purpose of life. In this context, Islamic religious education according to Al-Ghazali not only provides an understanding of religious teachings, but also encourages intellectual exploration and critical thinking. The integration of spirituality and knowledge creates students who are not only skilled in academics, but also have noble character and spiritual depth. Thus, the philosophy of Islamic religious education according to Al-Ghazali offers a holistic view of education, which aims to form individuals who are spiritually and intellectually balanced.